2012
DOI: 10.1371/journal.pone.0040812
|View full text |Cite
|
Sign up to set email alerts
|

An IP-10 (CXCL10)-Derived Peptide Inhibits Angiogenesis

Abstract: Angiogenesis plays a critical role in processes such as organ development, wound healing, and tumor growth. It requires well-orchestrated integration of soluble and matrix factors and timely recognition of such signals to regulate this process. Previous work has shown that newly forming vessels express the chemokine receptor CXC receptor 3 (CXCR3) and, activation by its ligand IP-10 (CXCL10), both inhibits development of new vasculature and causes regression of newly formed vessels. To identify and develop new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 24 publications
2
59
0
Order By: Relevance
“…However, we were unable to directly show either the effect of CXCR3 on VSMC migration or the effect of CXCL10 on HUVEC migration. Yates-Binder et al 24 already showed an inhibiting effect of an interferon-inducible protein 10 peptide on endothelial cell motility and tube formation, although showing this in a different cell type (human microvascular endothelial cells versus HUVECs).…”
Section: Discussionmentioning
confidence: 99%
“…However, we were unable to directly show either the effect of CXCR3 on VSMC migration or the effect of CXCL10 on HUVEC migration. Yates-Binder et al 24 already showed an inhibiting effect of an interferon-inducible protein 10 peptide on endothelial cell motility and tube formation, although showing this in a different cell type (human microvascular endothelial cells versus HUVECs).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CXCL10, via derived peptide [70], or AAV-CXCL10 vector can be topically applied to the ocular surface to reduce or prevent corneal angiogenesis associated with chemical injury and graft rejection, the latter of which is related to corneal lymphangiogenesis [7, 71]. …”
Section: Discussionmentioning
confidence: 99%
“…IP‐10, a DPP IV/CD26 substrate inactivated by its proteolytic activity, is a chemotactic proinflammatory cytokine and chemoattractant for monocytes and T lymphocytes with the ability to inhibit the proliferation of endothelial cells . It has been shown that IP‐10 inhibits angiogenesis and delays reepithelialization of wounds .…”
Section: Discussionmentioning
confidence: 99%